DEVELOPMENT OF THEORETICAL THINKING IN THE EDUCATIONAL PROCESS - Denysenko, Ye.V. (Pedagogy of Higher and Secondary Education, 2009)
The article reveals the actuality of the development of theoretical thinking, is structure and methods for the improvement of its formation.